Manfaat Kewirausahaan Sejak Dini Desa di Desa Labuan Salumbone - Pahman Pahman; Maharani K.A. Tjakunu; Rima Sukaena Al Aslamiah; Muh Dwiki Wiryawan; Moh. Riviadi Abdullah; Mutiara Eka Putri; Fauzan Afif; Mohammad Azman (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2025)
The purpose of this community service is to provide provisions and understanding for the community in Labuan Salumbone Village so that they have the skills, knowledge and attitude to enter the world of independent entrepreneurship as an effort to improve the economic welfare of the community. By giving lectures on the benefits of entrepreneurial activities, of course, it will provide encouragement and enthusiasm for the community to create business opportunities independently. This activity can also be a driver for the community to be economically independent. The target of this real work lecture program is to increase awareness of the world of Basic Education, especially children, to the community, in addition to being a motivation and inspiration for the village community through entrepreneurial activities. With good entrepreneurial knowledge, it is hoped that it will be able to foster a mature attitude of independence in trying to improve the economic standard of living of the village